Prostaglandin transporter mutations cause pachydermoperiostosis with myelofibrosis (2012)
Pachydermoperiostosis, or primary hypertrophic osteoarthropathy (PHO), is an inherited multisystem disorder, whose features closely mimic the reactive osteoarthropathy that commonly accompanies neoplastic and inflammatory pathologies. We previously described deficiency of the prostaglandin-degrading enzyme 15-hydroxyprostaglandin dehydrogenase (HPGD) as a cause of this condition, implicating elevated circulating prostaglandin E2 (PGE2) as causative of PHO, and perhaps also as the principal mediator of secondary HO. However, PHO is genetically heterogeneous. Here, we use whole-exome sequencing to identify recessive mutations of the prostaglandin transporter SLCO2A1, in individuals lacking HPGD mutations. We performed exome sequencing of four probands with severe PHO, followed by conventional mutation analysis of SLCO2A1 in nine others. Biallelic SLCO2A1 mutations were identified in 12 of the 13 families. Affected individuals had elevated urinary PGE2, but unlike HPGD-deficient patients, also excreted considerable quantities of the PGE2 metabolite, PGE-M. Clinical differences between the two groups were also identified, notably that SLCO2A1-deficient individuals have a high frequency of severe anemia due to myelofibrosis. These findings reinforce the key role of systemic or local prostaglandin excess as the stimulus to HO. They also suggest that the induction or maintenance of hematopoietic stem cells by prostaglandin may depend upon transporter activity. © 2012 Wiley Periodicals, Inc.